The unequal distribution of speaking time in parliamentary-party groups - Bäck, Hanna; Baumann, Markus; Debus, Marc; Müller, Jochen (Legislative studies quarterly, 2018)
Parliamentary debates provide an arena where Members of Parliament (MPs) present, challenge, or defend public policies. However, the “plenary bottleneck” allows the party leadership to decide who participates in a debate. We argue that in this decision the timing of a debate matters: in proximity of elections, the leadership should be concerned with maintaining its brand name and therefore restrict floor access, in particular if the debate is salient for the respective party. We evaluate our hypotheses in a cross-country study drawing on a novel data set covering all speeches given during one or two legislative terms in six European parliaments. We find that the electoral cycle matters for the distribution of speaking time: Party leaders do restrict parliamentary speechmaking to a smaller number of MPs at the end of the term. This has important implications for our understanding of parliaments as an electoral arena and for our understanding of intraparty politics.